Identifying and Prioritizing Implementation Barriers, Gaps, and Strategies Through the Nigeria Implementation Science Alliance: Getting to Zero in the Prevention of Mother-to-Child Transmission of HIV. (1st August 2016) - Ezeanolue, Echezona E.; Powell, Byron J.; Patel, Dina; Olutola, Ayodotun; Obiefune, Michael; Dakum, Patrick; Okonkwo, Prosper; Gobir, Bola; Akinmurele, Timothy; Nwandu, Anthea; Torpey, Kwasi; Oyeledum, Bolanle; et al.
Abstract : Background: In 2013, Nigeria accounted for 15% of the 1.3 million pregnant women living with HIV in sub-Saharan Africa and 26% of new infections among children worldwide. Despite this, less than 20% of pregnant women in Nigeria received an HIV test during pregnancy, and only 23% of HIV-infected pregnant women received appropriate intervention following HIV diagnosis. This article reports findings from 2 structured group exercises conducted at the first Nigeria Implementation Science Alliance Conference to identify (1) barriers and research gaps related to prevention of mother-to-child transmission (PMTCT) and (2) potential strategies and interventions that could address PMTCT challenges. Methods: Two 1-hour structured group exercises were conducted with 10 groups of 14–15 individuals (n = 145), who were asked to brainstorm barriers and strategies and to rank their top 3 in each category. Data analysis eliminated duplicate responses and categorized each of the priorities along the HIV care continuum: HIV diagnosis, linkage to care, or retention in care. Results: Participating stakeholders identified 20 unique barriers and research gaps related to PMTCT across the HIV continuum. Twenty-five unique interventions and implementation strategies were identified. Similar to the barriers and research gaps, these interventions and strategies were distributed across the HIV care continuum. Conclusions: The barriers and strategies identified in this study represent important pathways to progress addressing MTCT. The deliberate involvement of state and federal policy makers, program implementers, and researchers helps ensure that they are relevant and actionable.